INOVASI TATA KELOLA PEMERINTAHAN DAERAH DI KABUPATEN BANTAENG - Herman Dema; Nandang Alamsah D; Rahman Mulyaman; Mudiyati Rahmatunnisa (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2021)
This study discusses innovative governance which is an assessment of the acceleration and improvement of governance. The method used in this study is a qualitative method with a unit of analysis for the regional government of Bantaeng Regency. The technique of determining the informants is done by purposive, data collection with in-depth interview techniques, observations, documentation, webinars, and online data. Data analysis includes several stages, namely data reduction, data presentation, after the selected data is analyzed using Nvivo 12 plus, and then conclusions are drawn. The results showed that the factors that determine the success of local governance are (1) leaders & leadership, (2) institutions, (3) modernization of the public sector, (4) organized civil society, (5) democratic traditions or culture, (6 ) the level of public trust, and (7) factors of communication, coordination, and synergy. Building innovative local governance requires several strategies, namely community involvement, utilization of cooperation, integrated services, utilization of information technology, and decentralization. To accelerate governance innovation, it is recommended to apply a collaborative model between institutions/agencies and determine the theme in each program and activity.